The distances of cultural intermediation: Specialized journalistic critique versus popular taste - García-Borrego, Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article studies the differences between the judgment of cultural journalists and the taste of readers by applying a content analysis to the “books of the year” recommended by the main Spanish supplements (‘ABC Cultural’, ‘Babelia’, ‘Cultura|s’ and ‘El Cultural’) between 2010 and 2020 (n=1,133), and comparing these listings with the ratings of ‘Goodreads’ users. The selected works receive a modest average score (7.3) —only 0.2% of them can be considered “outstanding”—, which shows the existing (although decreasing) distance between public and critics, especially when the variables of nationality and gender of the author are taken into account.